Does Living Remotely Imply Tacit Approval to Diminished Health Services? - Banyai, Mark (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
Most of the Canadian population lives in urban settings where amenities, including rapid access to major hospitals and tertiary care, are readily available. However, a significant yet often overlooked segment of the population resides in remote areas, where daily life is markedly different, and accessing healthcare poses considerable challenges. As our society progresses toward truth and reconciliation with Canada’s Indigenous peoples, it is crucial to reconsider and critically address the prevailing narrative surrounding remote living. In my interactions with non-Indigenous individuals living off reserves, many appear to view remote living as a personal choice, accepting that limited access to healthcare is an unavoidable consequence. However, I argue that Indigenous peoples were not — and still are not — offered a genuine “choice” regarding where they can live and, therefore, do not tacitly consent to reduced healthcare services.